Strategy To Improve Wuling Car Brand Image Through Quality Strengthening Product, Price Perception and Word of Mouth in Banten Province - Ferdiansyah, Ferdiansyah; Diposumarto, Ngadino Surip; Muharram, Hari (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This research aims to analyze the influence of product quality, price perception, product innovation, and word of mouth (WOM) on the brand image of Wuling cars in Banten Province using the structural equation modeling-partial least squares (SEM-PLS) approach. The research results show that all the proposed hypotheses are accepted. Product quality has a significant influence on WOM with attractive car design as the main indicator, which is supported by promotions such as discounts. The perception that prices are commensurate with product benefits has also been proven to increase WOM, especially through relevant discount strategies. Product innovation, such as the development of new car types, significantly drives positive WOM, strengthening Wuling's brand image. In addition, WOM plays an important role in mediating the influence of product quality, price perception, and product innovation on brand image. In the context of brand image, an attractive car design is the main element that creates a positive impression in the eyes of consumers. This research makes a significant contribution to the marketing literature by integrating five main variables in a comprehensive analytical framework. The practical implications include a focus on product innovation, competitive pricin